Implementasi Program Roots Indonesia dalam Mengatasi Perilaku Bullying di SMKN 1 Rejotangan Kabupaten Tulungagung - Istighfaria, Maya Adelina; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2024)
This research aims to describe the implementation of the Indonesian roots program at SMKN 1 Rejotangan, Tulungagung Regency, and identify obstacles in implementing the Indonesian roots program at SMKN 1 Rejotangan, Tulungagung Regency. This research uses a descriptive qualitative approach with a case study method. The theory used in this research is George C. Edward III's theory of policy implementation. Data collection techniques in this research used observation, interviews and documentation. The informants in this research consisted of the Principal, Deputy Head of Student Affairs, Counseling Guidance Teacher/Facilitator Teacher, change agent students, and several student representatives from classes X, XI, XII of SMKN 1 Rejotangan. The data analysis technique in this research uses the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results obtained in this research indicate that the implementation of the Indonesian roots program at SMKN 1 Rejotangan consists of several stages, namely (1) Selection of teacher facilitators, (2) Training of teacher facilitators, (3) Initial survey and selection of students as agents of change, ( 4) Training for students as agents of change, (5) Actions for students as agents of change and teacher facilitators, (6) Student-based actions which include outreach, declarations, anti-bullying campaigns, and art and work performances. Obstacles in implementing the Indonesian roots program at SMKN 1 Rejotangan include the difficulty of regenerating teacher facilitators, limited interaction with implementers, parents' doubts about the role of students as agents of change, difficulties in arranging training schedules, low student awareness of the dangers of bullying, and limited financial resources for support program needs. Keywords: Implementation, Roots Indonesia Program, Bullying Behavior.